Professionalization in low-threshold drug aid - between managerialism and practitioner knowledge - Joachim Thönnessen; Christiane Westerveld (Social Work & Society, 2022)
This article deals with the socio-political effects of a development toward more "managerialism" that has taken place over several decades up to the present day. Using the practical example of low-threshold drug help, it asks to what extent this service, which is based on empathy, contact and resonance, is compatible with the movement toward a business model that is profitable for users, providers and funding bodies. The method is based on ideal-typical case descriptions, personal experience and a theoretical analysis of relevant literature on the topics of "management" and "low-threshold addiction support". The article refers primarily to developments in the German context, but can - with certain qualifications - also be used to describe developments in comparable countries.